WOMEN BEFORE THE LAW: BETWEEN JUSTICE AND CERTAINTY: NOTES ON DIVORCE SETTLEMENT CASE DUE TO DOMESTIC VIOLENCE IN METRO RELIGIOUS COURT - Wijayati, Mufliha; Rosadi, Aden (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
Family case settlement in the religious court often does not run effectively and efficiently due to some judicial constraints in the level of absolute competence, event law, and material law. This paper seeks to describe some notes related to divorce settlement due to the domestic violence in the religious court. The data was collected through the observation of the trial and the reading of the verdicts on several divorce cases of domestic violence in metro religious court in 2016-2018. The findings suggest that justice for women could only be gained at a formal legal level, while the desired substantive justice has not yet been achieved. The constraints occur in such stages as submission, case handling, and the verdict. The gender perspective of justice case handling and the judges’ courage of the religious court to deliver ultra petitum verdicts are a legal breakthrough in order to realize substantive justice in resolving family conflicts. Keywords: divorce, domestic violence, legal certainty, legal justice, religious court